2020
DOI: 10.1007/s11096-020-01069-2
|View full text |Cite
|
Sign up to set email alerts
|

Identifying patients with metformin associated lactic acidosis in the emergency department

Abstract: Background Metformin associated lactic acidosis (MALA) is a serious adverse event with a high mortality rate of 30–50%. Early recognition of MALA and timely starting treatment may reduce its morbidity and mortality. Objective The aim of this study was to explore clinical parameters to identify patients with MALA in patients with suspected sepsis induced lactic acidosis in the emergency department ED. Setting A retrospective single centre study was conducted at the Deventer Teaching Hospital in the Netherlands.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…MALA has been reported to occur at up to 138 per 100,000 patients per year [ 25 ]. It should be noted that early diagnosis of MALA is critical, and it should be suspected in patients with creatinine concentrations of 256 mol/l or higher and lactate concentrations of 8.4 mmol/l or higher [ 26 ]. MALA pathogenesis is attributed to a mitochondria blockage of the complex 1 respiratory chain [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…MALA has been reported to occur at up to 138 per 100,000 patients per year [ 25 ]. It should be noted that early diagnosis of MALA is critical, and it should be suspected in patients with creatinine concentrations of 256 mol/l or higher and lactate concentrations of 8.4 mmol/l or higher [ 26 ]. MALA pathogenesis is attributed to a mitochondria blockage of the complex 1 respiratory chain [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 20 23 ] Diagnostically, the combined presence of acute renal failure, pH ≤7.35, lactate ≥8.4 mmol/L, and known use of metformin is sensitive and specific for MALA. [ 41 ] Once identified, the treatment is supportive with the use of IV fluids, vasopressors, and dextrose drips. [ 35 39 ] Most important is the immediate implementation of dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have compared CRRT, conventional HD, and SLED, all of which have shown benefit in the treatment of MALA. [ 36 37 38 39 41 ] ECMO may provide the necessary hemodynamic support if dialysis and supportive care are insufficient. [ 25 ]…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the actual diagnosis of LA is difficult without information that metformin was used. As reported by van Berlo-van de Laar IRF et al, the sensitivity of identifying metformin-associated LA in patients with sepsis-induced lactic acidosis suspected is 85% when even using the recommended parameters (lactate ≥ 8.4 mmol/L, creatinine ≥ 256 μmol/L), and a specificity is 95% [ 41 ]. Under this circumstance, underreporting cases should be considered.…”
Section: Discussionmentioning
confidence: 99%